INSIGHTS OF AL-QUR’AN ABOUT WORSHIP IN EDUCATIONAL AND MERDEKA BELAJAR REVIEWS IN INDONESIA (AN EFFORT TO REALIZE INDEPENDENT AND PEDAGOGICAL HUMANS) - Ahmad Mujahid; Usri Usri (Balai Penelitian dan Pengembangan Agama Makassar, 2022)
AbstractThe dehumanization of education has an impact on the orientation of human worship to become very materialistic. Therefore, an educational concept is needed to return humans to become independent pedagogical beings in globalization. This study will dissect the insight of the Qur'an on worship from the education perspective and free learning concept as an effort to create an independent human being. The type of this research is library research with the maudhu'i interpretation method through a semantic approach. The results found from this study are first, the Qur'an confirms that humans were created only to worship, thus it can be understood that worship is the purpose of human creation as an independent pedagogic creature. The second principles of education are in line with the concept of worship, namely lifelong worship which is a role model for Rabbani education. Third, the benefit obtained by people who worship properly will reach the highest peak of taqwa life and it is the morality of education. If humans guide and practice the message of the Qur'an, they will be able to become independent pedagogical beings. Keywords: Worship, Education, Independent